Cultural learning process: lesson from microhistory. Issue 4 (20th May 2021) - Yu, Tianyuan; Mills, Albert J.
Abstract : Purpose: The purpose of this paper is to examine the cultural learning process (namely, the development, practice and enhancement of cultural intelligence (CQ)) of a successful entrepreneur – Harold Bixby, a Pan American Airways expatriate, as reflected in the memoir of his experiences in China during 1933–1938. Design/methodology/approach: This study adopts a microhistory approach as a methodology for studying history and the past while ultimately requiring evaluations informed by the present. This paper first identifies the literature gap on CQ development and the need to study historical accounts of the past in assessing the CQ development process. This study then outlines the four key foci of microhistory as a heuristic for making sense of on-going and past accounts of selected phenomena. Findings: This paper finds that specific personality traits (namely, openness to experience and self-efficacy), knowledge accumulation through deep cultural immersion (namely, extensive reading/study, visiting/observation and interacting/conversation), critical incident and metacognition all contributed to Bixby's CQ development, which was a time-consuming process. Originality/value: The study contributes to debates around cultural learning and historical organization studies by providing a rich, qualitative study of CQ assessment and CQ development through microhistory. This study highlights the importance of cognitive CQ and the function of extensive reading/studying in the process of knowledge accumulation. This paper draws attention to critical incidents as an underexplored way of learning tacit knowledge. Moreover, this study suggests metacognitive CQ can be enhanced through meditative and reflexive teaching and research practices. These findings have significant implications for cross-cultural training programs.